Playing the software archeologist : Exploring and conquering an unknown legacy systems - Risi, Walter A. (2001)
Understanding and modifying unknown legacy systems is a task that has challenged software engineers for years. While conventional approaches like reverse engineering and reengineering are well known and proven effective, there are cases where these techniques are too heavyweight or time-consuming. This position paper shows an example of a real situation in which we had to add functionality to an existing legacy system while dealing with a tight schedule. We share our experience and a few techniques that we found useful while digging in the depths of legacy code. We follow the software archeology metaphor and present our techniques as ways to explore and conquer unknown systems.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 12/03/2009)
OOPSLA 2001. Software Archeology Workshop. October 2001.
Keywords: MANTENIMIENTO DE SOFTWARE